2019
DOI: 10.4103/ijpsym.ijpsym_464_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Adult ADHD Co-morbidity in Alcohol Use Disorders in a General Hospital Setup

Abstract: Background:Attention deficit hyperactive disorder (ADHD) symptoms persisting into adulthood can influence the course and outcome of alcohol use disorders (AUDs). A cross-sectional study was conducted to assess the prevalence of adult ADHD in patients admitted with AUDs in a general hospital setup.Methods:In this study, 100 consecutive inpatients with alcohol use disorder (AUD) were evaluated for the diagnosis of ADHD. Patients with AUD were assessed with Severity of Alcohol Dependence Questionnaire, Clinical I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 21 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…This fits the results of the aforementioned meta-analysis (2012), which demonstrated a higher prevalence of ADHD among patients with OUD and alcohol use disorder than among patients with cocaine use disorder [13]. There were many studies among patients with alcohol use disorder over the years, showing similar results with a high ADHD prevalence (about 20%) [25,[29][30][31][32][33]. Recent studies in patients with benzodiazepine use disorder show even higher ADHD prevalence rates, which lie between 31% [34] and 39% [35,36], but there are also studies in populations of patients with cocaine use disorder showing high ADHD prevalence between 14% [37] and 20% [38].…”
supporting
confidence: 87%
“…This fits the results of the aforementioned meta-analysis (2012), which demonstrated a higher prevalence of ADHD among patients with OUD and alcohol use disorder than among patients with cocaine use disorder [13]. There were many studies among patients with alcohol use disorder over the years, showing similar results with a high ADHD prevalence (about 20%) [25,[29][30][31][32][33]. Recent studies in patients with benzodiazepine use disorder show even higher ADHD prevalence rates, which lie between 31% [34] and 39% [35,36], but there are also studies in populations of patients with cocaine use disorder showing high ADHD prevalence between 14% [37] and 20% [38].…”
supporting
confidence: 87%
“…After applying a diagnostic interview using DSM 5 in these subjects, ADHD diagnosis was confirmed in 19% (n = 19) of the subjects. 14…”
Section: Discussionmentioning
confidence: 99%
“…6 It is speculated that the disabling characteristics of ADHD in adulthood may contribute to the onset or exacerbation of other psychiatric comorbidities, including substance use disorders. 7,8 Numerous studies have reported that patients with comorbid ADHD and substance use disorders exhibit greater substance use and more severe psychiatric symptoms, [9][10][11] including more intense cravings that could increase the risk of relapse. 12 A study comparing AUD relapse risk between subjects with and without ADHD traits showed a higher risk of relapse in the ADHD group.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that patients with comorbid ADHD and substance use disorders exhibit greater substance use and more severe psychiatric symptoms, 9–11 including more intense cravings that could increase the risk of relapse 12 . A study comparing AUD relapse risk between subjects with and without ADHD traits showed a higher risk of relapse in the ADHD group 13 .…”
Section: Introductionmentioning
confidence: 99%